Beyond relativism : Raymond Boudon, cognitive rationality, and critical realism - Hamlin, Cynthia Lins, 1969- (Routledge studies in critical realism, 2002)
Cynthia Lins Hamlin persuasively argues that critical realism represents a better safeguard against the relativism which springs from the conflation of social reality and our ideas about it.